Study clinical response and parasite clearance response to Artemisinins in severe malaria in children - Ghanghoriya, Pawan; Srivastava, Purusharth; K. Bharti, Praveen (International Journal of Contemporary Pediatrics, 2018)
Background: The research was conducted to study the clinical response and parasite clearance response to Artesunate therapy, in children admitted with severe malaria at a tertiary care centre in Central India. Methods: It is a prospective analytical study. 18 microscopy positive children diagnosed with severe malaria were included. Baseline blood samples collected for microscopy and biochemical tests. All patients were administered standard intravenous Artesunate therapy and were watched every 12 hourly for: 1. Resolution of clinical signs and symptoms. Clinical parameters included level of consciousness in form of GCS, vital signs like pulse rate, respiration, signs of bleeding, development of icterus, pallor, urine output and laboratory parameters included blood sugar levels, renal and liver function tests. 2. Time taken for conversion of microscopic Smear positive to Smear negative. Results: The mean age was 8.34±4.35 years. Males and females were equally affected. 61% of severe malaria patients were infected by P. falciparum and remaining were infected by P. vivax. The most common clinical features were Pallor: 100%, Respiratory distress: 66.7%, Cerebral malaria: 55.6%. After giving Artesunate therapy, Mean GCS in Cerebral malaria patients showed improvement (on admission: 9±1.15, at 72 hours: 12.5±3.7). Effect was marginally better in P. vivax cases. Respiratory distress and tachycardia improved in majority of patients (75% and 80% respectively). The number of patients with icterus progressively increased. Improvement in liver function and renal function was minimal. 100% parasite clearance was achieved. The mean parasite clearance time is 46±9.43 hours. 72.2% were successfully discharged, 22.2% took Leave Against Medical Advice (LAMA) and 5.6% certified dead. Conclusions: Artesunate is an effective drug in severe malaria patients in terms of rapid improvement of cerebral function, improvement and stabilization of vitals, parasite clearance with favorable long-term outcome. There is no evidence of plasmodium resistance to Artesunate currently as per the present study.